2018
DOI: 10.1002/ejoc.201800911
|View full text |Cite
|
Sign up to set email alerts
|

Application of 1,3‐Dipolar Reactions between Azomethine Ylides and Alkenes to the Synthesis of Catalysts and Biologically Active Compounds

Abstract: The (3+2) cycloaddition between azomethine ylides and alkenes is an efficient, convergent and stereocontrolled method for the synthesis of unnatural pyrrolidine and proline scaffolds. In this review, the application of this reaction to the synthesis of enantiopure organometallic ligands for asymmetric catalysis is presented first. These new EhuPhos ligands can participate in a second generation of 1,3‐dipolar reactions that generate an offspring of unnatural proline derivatives that behave as efficient organoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 103 publications
0
24
0
Order By: Relevance
“…The second approach to the 2‐(hetero)arylpyrrolidines is based on the formation of pyrrolidine ring from acyclic precursors. Within this approach, intermolecular cycloaddition reactions play a significant role, [3+2] dipolar cycloadditions being the most used ones . The methods based on the intramolecular cyclization of acyclic precursors are also widely used, especially in the case of polycyclic systems .…”
Section: Introductionmentioning
confidence: 99%
“…The second approach to the 2‐(hetero)arylpyrrolidines is based on the formation of pyrrolidine ring from acyclic precursors. Within this approach, intermolecular cycloaddition reactions play a significant role, [3+2] dipolar cycloadditions being the most used ones . The methods based on the intramolecular cyclization of acyclic precursors are also widely used, especially in the case of polycyclic systems .…”
Section: Introductionmentioning
confidence: 99%
“…The full reaction pathway was investigated with the substrates 33 , 1a (R 1 = Ph, R 2 = H) and a simplified ligand ( R )- 2a (methyl groups were used instead of phenyl groups on the phosphorus). The DFT calculations indicated that the Ag­(I)/( R )- L2a -catalyzed 1,3-DC of β-sulfonyl acrylates proceeded via a stepwise Michael addition/Mannich pathway . The calculations also revealed that the two H-bonding interactions between the two electron-withdrawing groups of the ( Z )-sulfonyl acrylate and the NH 2 group of the chiral ligand accounted for the high endo -selectivity (Scheme b).…”
Section: Catalytic Asymmetric 13-dipolar Cycloaddition Of N-metallate...mentioning
confidence: 97%
“…[ 3–6 ] In simple, the pyrrole derivative of interest can be synthesized just by tuning azomethineylide and dipolarophile. [ 7–9 ] In addition to this, they may react with carbonyl compounds to yield oxazolidine derivatives. [ 10,11 ] Hence many reports are available in the literature for such cycloadditions, especially by using electron‐deficient alkenes and alkynes as dipolarophiles such as α,β‐unsaturated carbonyl compounds and nitro compounds.…”
Section: Introductionmentioning
confidence: 99%